A Review on Stability Challenges and Probable Solution of Perovskite–silicon Tandem Solar Cells - Hossain, Md Momin; Khan, Md Yakub Ali; Halim, Md. Abdul; Elme, Nafisa Sultana; Hussain, Md. Nayeem (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
Perovskite-silicon tandem solar cells have shown great potential in increasing the efficiency of solar cells, with efficiencies reaching as high as 25%. However, the stability of these cells remains a major challenge that must be addressed before they can be commercialized. This review focuses on the stability challenges of perovskite-silicon tandem solar cells and possible solutions to address these challenges. The main stability issues include the instability of the perovskite layer, the degradation of the silicon layer, and the failure of the interfaces between the layers. One solution is to use more stable perovskite materials, such as methylammonium lead iodide (MAPbI3) or formamidinium lead iodide (FAPbI3), which have shown better stability than traditional perovskite materials. Another solution is to use passivating layers, such as titanium dioxide, to protect the perovskite layer from degradation. Another solution is to use silicon heterojunction (SHJ) solar cells, which have shown better stability than traditional silicon solar cells. In addition, the use of encapsulation techniques, such as using a barrier layer or a hermetic seal, can help to protect the tandem solar cell from environmental degradation. In order to improve the stability of perovskite-silicon tandem solar cells, it is important to continue research on the development of more stable perovskite materials, passivating layers, and encapsulation techniques. Additionally, further research is needed to understand the mechanisms of degradation and to develop methods for monitoring and mitigating the degradation of the tandem solar cells.